Chlorella vulgaris and Haematococcus pluvialis biomass as colouring and antioxidant in food emulsions - Sousa, Isabel (2010)
The use ofmicroalgal biomass, a natural ingredi- ent, to colour oil-in-water pea protein stabilised emulsions was studied. Various levels of incorporation of Chlorella vulgaris green, Chlorella vulgaris orange (after caroteno- genesis), andHaematococcus pluvialis (red, after caroteno- genesis) were used, resulting in a wide range of appealing colours from green to orange and pink. The colour stability of the emulsionswas evaluated, through the evolution of the L∗a∗b∗ parameters (CIELAB system) along 6 weeks. The primary and secondary oxidation products of the emulsions were also determined, and an enhanced resistance to oxi- dation was evidenced by emulsions containing microalgae. Therefore antioxidant functionality was another positive aspect of its use as an ingredient. Colour stability, a va- riety of attractive hues, and added resistance to oxidation ensure an adequate compromise of sensory and functional properties for these novel emulsions.